Interview with Dr. Beverley Foulks McGuire on video-gaming, Buddhism, and death - Borchert, John W. (Gamevironments, 2018)
Dr. Beverley Foulks McGuire speaks with editor John W. Borchert about her new research on video-gaming, death, and Buddhism.